MiR155-5p in adventitial fibroblasts-derived extracellular vesicles inhibits vascular smooth muscle cell proliferation via suppressing angiotensin-converting enzyme expression - Xing-Sheng Ren; Ying Tong; Yun Qiu; Chao Ye; Nan Wu; Xiao-Qing Xiong; Jue-Jin Wang; Ying Han; Ye-Bo Zhou; Feng Zhang; Hai-Jian Sun; Xing-Ya Gao; et al. (Journal of Extracellular Vesicles, 2020)
Proliferation of vascular smooth muscle cells (VSMCs) plays crucial roles in vascular remodelling and stiffening in hypertension. Vascular adventitial fibroblasts are a key regulator of vascular wall function and structure. This study is designed to investigate the roles of adventitial fibroblasts-derived extracellular vesicles (EVs) in VSMC proliferation and vascular remodelling in normotensive Wistar-Kyoto rat (WKY) and spontaneously hypertensive rat (SHR), an animal model of human essential hypertension. EVs were isolated from aortic adventitial fibroblasts of WKY (WKY-EVs) and SHR (SHR-EVs). Compared with WKY-EVs, miR155-5p content was reduced, while angiotensin-converting enzyme (ACE) content was increased in SHR-EVs. WKY-EVs inhibited VSMC proliferation of SHR, which was prevented by miR155-5p inhibitor. SHR-EVs promoted VSMC proliferation of both strains, which was enhanced by miR155-5p inhibitor, but abolished by captopril or losartan. Dual luciferase reporter assay showed that ACE was a target gene of miR155-5p. MiR155-5p mimic or overexpression inhibited VSMC proliferation and ACE upregulation of SHR. WKY-EVs reduced ACE mRNA and protein expressions while SHR-EVs only increased ACE protein level in VSMCs of both strains. However, the SHR-EVs-derived from the ACE knockdown-treated adventitial fibroblasts lost the roles in promoting VSMC proliferation and ACE upregulation. Systemic miR155-5p overexpression reduced vascular ACE, angiotensin II and proliferating cell nuclear antigen levels, and attenuated hypertension and vascular remodelling in SHR. Repetitive intravenous injection of SHR-EVs increased blood pressure and vascular ACE contents, and promoted vascular remodelling in both strains, while WKY-EVs reduced vascular ACE contents and attenuated hypertension and vascular remodelling in SHR. We concluded that WKY-EVs-mediated miR155-5p transfer attenuates VSMC proliferation and vascular remodelling in SHR via suppressing ACE expression, while SHR-EVs-mediated ACE transfer promotes VSMC proliferation and vascular remodelling.